The Level Of Creative Thinking Among Fifth-Grade Students Of Primary Education In The City Of Touggourt (Algeria) (مجلة الواحات للبحوث والدراسات, 2025)
The Current Study Aims To Reveal The Level Of Creative Thinking Among Fifth-Grade Students In The Fourth Educational District In The City Of Touggourt. To Achieve The Objectives Of The Study, The Descriptive Exploratory Method Was Used, Where The Torrance Test Of Creative Thinking, Form A, Consisting Of Three Activities Covering Four Dimensions (Fluency, Flexibility, Originality, And Detail), Was Applied. A Simple Random Sample Was Selected From The Fourth Educational District In Touggourt, Including 130 Students, Of Whom 70 Were Female. After Collecting Data And Analyzing The Results Using The SPSS V20 Statistical Package For Social Sciences, The Results Showed That The Level Of Creative Thinking Among Fifth-Grade Students Was Low. The Results Also Indicated Significant Differences In Creative Thinking Between Male And Female Students, With Females Showing Higher Levels Of Creativity.Keywords: Creative Thinking; Fifth-Grade Students.